Early Detection of Cardiovascular Risk Factors and Definition of Psychosocial Profile in Women Through a Systematic Approach: The Monzino Women Heart Center's Experience - Gili, Sebastiano; Giuliani, Mattia; Santagostino Baldi, Giulia; Teruzzi, Giovanni; Pravettoni, Gabriella; Montorsi, Piero; Trabattoni, Daniela (Frontiers in Cardiovascular Medicine, 2022)
Introduction Cardiovascular (CV) disease is the leading mortality cause among women, yet an alarming misrepresentation of women in CV studies and a low awareness of the impact of CV among women still persist to date. The Monzino Women Heart Center has been established as a clinical and research program dedicated to primary prevention of CV disease in women. Methods Patients aged between 35 and 60 years and with no history of CV disease underwent a comprehensive evaluation including a cardiologic outpatient visit with electrocardiogram, individual CV risk calculation, first-level cardiovascular examinations and a psychological assessment. Results A total of 635 women, with a mean age of 52.2 ± 6.4 participated to the project on a voluntary basis during the period January 2017–August 2021. Included patients had a high level of education (40.4% with a graduate or postgraduate university degree), the majority of them, in a stable couple and with children, were actively working. More than half of the patients performed physical activity on a regular basis. Prevalence of traditional CV risk factors were family history (70.2%), hypertension (46%), hypercholesterolemia (22%) and diabetes (14%). Early or premature menopause was reported by 17.7% of the patients, gestational hypertension and diabetes by 4.96 and 1.7%, respectively. Symptoms of depression were reported by 27%; nearly 36% of the participants rated high score of state anxiety and 41% of trait anxiety. Nearly 69% of the participants showed moderate-to-high perceived stress. The mean value of perceived general self-efficacy was moderate (mean = 28.78, SD = 4.69). Conclusion A CV prevention program dedicated to women can help identifying a considerable number of patients with risk factors for whom early interventions can help reducing the risk of developing CV disease. Psychological assessment might unmask depression or anxiety disorders, which might have a potential long-terme detrimental effect on CV health.